2012
DOI: 10.1007/s00284-012-0209-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of Luciferase Expressing Leishmania donovani Axenic Amastigotes as Primary Model for In Vitro Screening of Antileishmanial Compounds

Abstract: The development of new therapeutic leads against leishmaniasis relies primarily on screening of a large number of compounds on multiplication of clinically irrelevant transgenic promastigotes. The advent of the successful in vitro culture of axenic amastigotes allows the development of transgenic axenic amastigotes as a primary screen which can test compounds in a high throughput mode like promastigotes, still representative of the clinically relevant mammalian amastigotes stage. The present study reports the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Axenic amastigotes have also been screened by means of HTS platforms [9], [51], [52]. However, expression arrays comparing both axenic amastigotes and those isolated from infected macrophages have shown metabolic differences, impaired intracellular transport and altered response to oxidative stress [53].…”
Section: Discussionmentioning
confidence: 99%
“…Axenic amastigotes have also been screened by means of HTS platforms [9], [51], [52]. However, expression arrays comparing both axenic amastigotes and those isolated from infected macrophages have shown metabolic differences, impaired intracellular transport and altered response to oxidative stress [53].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] These screens generally employ transgenic Leishmania lines expressing either fluorescent (e.g., GFP) or bioluminescent (e.g., luciferase) reporter proteins and quantify intracellular growth in infected macrophages from total well fluorescence/luminescence, or the shift in host cell fluorescence by flow cytometry. 15,[18][19][20][21][22][23][24][25] However, per-well measurements cannot distinguish between intracellular and extracellular parasites, and in some studies, the reported IC 50 s for known drugs, using a flow cytometry-based method, are considerably greater than those reported with other assays. 21 More recent studies have used high-content screening (HCS) approaches to monitor the intracellular growth of transgenic parasite lines within individual macrophages, providing greater insights into host-parasite interactions and drug toxicity.…”
mentioning
confidence: 69%
“…Several studies about intracellular pathogenic microorganisms like Leishmania have indicated that independent reporter genes, such as GFP or luciferase, practically facilitate antimicrobial drug and cell biological activity research both in vitro and in vivo [ 7 , 8 , 20 , 25 , 26 ]. Dual reporter gene-expressing pathogens were then generated to more benefit the reporter activity [ 21 , 22 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…GFP is intrinsically fluorescent and can be detected easily and directly, without the need for any extra processing, by several instruments such as the fluorescent microscope, fluorimeter, and fluorescence-activated cell sorting (FACS). Among different reporter genes, LUC has been introduced as a more efficient reporter in the HTS mode [ 16 , 19 ] for drug screening [ 20 ] due to its high sensitivity and low background.…”
Section: Introductionmentioning
confidence: 99%